Evaluation of the blood lactate response in a simulation of the fifth section of the Hakon Ekiden using a runner-motion-response type treadmill - Terao, T.; Onda, T.; Sandhu, A.; Saito, M. (Österreichisches Journal für Sportmedizin, 2001)
The purpose of this study is to elucidate the blood lactate response in a simulation of the fifth section of the Hakon Ekiden (20,7 km) using a runner-motion-response type treadmill in a laboratory. 5 long diatnce runners built the experimental group, 5 triathletes were the control group. The results of the experiment show that most of the distance runners during the fifth section of the Hakon Ekiden are mainly supplied by the carbohydrate component and blood lactate showed 4 mmol/l at any point , with a higher intensity of physical activity at this point.